2015
DOI: 10.1002/cncr.29404
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic evidence of a strong association between non‐Hodgkin lymphoma and simian virus 40

Abstract: BACKGROUND: Non-Hodgkin lymphoma (NHL), the most common cancer of the lymphatic system, is of unknown etiology. The identification of etiologic factors in the onset of NHL is a key event that could facilitate the prevention and cure of this malignancy. Simian virus 40 (SV40) has been considered an oncogenic agent in the onset/progression of NHL. METHODS: In this study, an indirect enzyme-linked immunosorbent assay with 2 synthetic peptides that mimic SV40 antigens of viral capsid proteins 1 to 3 was employed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 40 publications
(101 reference statements)
2
26
0
Order By: Relevance
“…Independent analyses reported the detection of SV40 DNA sequences and viral neutralizing and IgG antibodies in healthy subjects, including in children, adolescents, adults, elderly individuals, and pregnant women [ 1 6 ]. Similar investigations detected SV40 markers in patients affected by cancers of different histotypes [ 7 14 ].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Independent analyses reported the detection of SV40 DNA sequences and viral neutralizing and IgG antibodies in healthy subjects, including in children, adolescents, adults, elderly individuals, and pregnant women [ 1 6 ]. Similar investigations detected SV40 markers in patients affected by cancers of different histotypes [ 7 14 ].…”
Section: Introductionsupporting
confidence: 59%
“…We have recently contributed to this goal by developing an innovative indirect enzyme-linked immunosorbent assay (ELISA) with synthetic peptides, which mimic antigens of the viral capsid proteins 1, 2 and 3 (VPs 1–3). This indirect ELISA is specific for the detection of SV40 antibodies in human sera and does not react with different genetic variants of the closely related human polyomaviruses BKPyV and JCPyV or with other less-homologous human polyomaviruses [ 1 4 , 8 , 10 12 , 14 ]. Immunologic data obtained with this assay indicated that the prevalence of SV40 serum IgG antibodies in healthy adults is approximately 18%, whereas antibody prevalence is significantly higher (2–3 times) in patients affected by SV40-associated tumors [ 1 4 , 8 , 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are other microorganisms involved in lymphomas like the Epstein-Barr virus (EBV), hepatitis C and Helicobacter pylori (amongst others). According to Tognon et al [ 13 ], we need to add simian virus 40 (SV40) to the list. In serum samples from NHL-affected patients ( n = 150) along with controls represented by patients with other cancers ( n = 142) and healthy subjects ( n = 300), they found antibodies against SV40 in about 40 % of the NHL patients, 20 % in other cancer patients and 15 % in healthy individuals.…”
Section: Epidemiology Of Lymphomamentioning
confidence: 99%
“…According to Tognon et al [13], we need to add simian virus 40 (SV40) to the list. In serum samples from NHL-affected patients (n=150) along with controls represented by patients with other cancers (n= 142) and healthy subjects (n=300), they found antibodies against SV40 in about 40 % of the NHL patients, 20 % in other cancer patients and 15 % in healthy individuals.…”
Section: Epidemiology Of Lymphomamentioning
confidence: 99%